2022
DOI: 10.2147/jir.s382876
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Neutrophil-to-Lymphocyte Ratio/Lymphocyte-to-Monocyte Ratio and In-Hospital Clinical Outcomes in Ischemic Stroke Treated with Intravenous Thrombolysis

Abstract: Objective Investigations on neutrophil-to-lymphocyte ratio (NLR) and lymphocyte-to-monocyte ratio (LMR) in patients with ischemic stroke are insufficient. We aimed to investigate the relationship of NLR and LMR with in-hospital clinical outcomes at different time points in ischemic stroke patients treated with intravenous tissues plasminogen activator (IV tPA). Methods We retrospectively enrolled patients who received IV tPA therapy within 4.5 hours from symptoms onset.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“… 27 Li et al demonstrated that the LMR 48 h after intravenous thrombolysis can be used as a biomarker of the functional outcome of discharged patients with AIS. 28 Our findings suggest that a low LMR increases the incidence of poor functional outcomes in AIS patients at discharge. This may be the first time that a correlation has been proposed between LMR at admission and functional outcome at discharge in patients with AIS.…”
Section: Discussionmentioning
confidence: 55%
“… 27 Li et al demonstrated that the LMR 48 h after intravenous thrombolysis can be used as a biomarker of the functional outcome of discharged patients with AIS. 28 Our findings suggest that a low LMR increases the incidence of poor functional outcomes in AIS patients at discharge. This may be the first time that a correlation has been proposed between LMR at admission and functional outcome at discharge in patients with AIS.…”
Section: Discussionmentioning
confidence: 55%
“…NLRs, calculated from neutrophils and lymphocytes, were found to be closely related to the effects of neutrophils and lymphocytes on stroke and their interaction mechanisms (Brooks et al., 2014 ; Li et al., 2022 ; Parikh et al., 2020 ; Ramiro et al., 2018 ). Prior studies showed that NLR was used to predict the prognosis of patients with AIS after thrombolysis in stroke patients (Brooks et al., 2014 ; Li et al., 2022 ; Maestrini et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…NLRs, calculated from neutrophils and lymphocytes, were found to be closely related to the effects of neutrophils and lymphocytes on stroke and their interaction mechanisms (Brooks et al., 2014 ; Li et al., 2022 ; Parikh et al., 2020 ; Ramiro et al., 2018 ). Prior studies showed that NLR was used to predict the prognosis of patients with AIS after thrombolysis in stroke patients (Brooks et al., 2014 ; Li et al., 2022 ; Maestrini et al., 2015 ). Most studies have collected the NLR value at several time points within 7 days after IVT (generally at admission, 24, 48 h, and 7 days) (Chu et al., 2020 ; Guo et al., 2016 ) and found that NLR level increased after stroke onset and reached the peak at 12–48 h (Li et al., 2022 ; Sadeghi et al., 2022 ; Shi et al., 2018 ; Weng et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations